Analisis SWOT Sebagai Dasar Penentu Strategi Bersaing Radio Suara Salatiga - Yusuf, Mohammad; Utomo, Hardi (Graduasi: Jurnal Bisnis & Ekonomi, 2015)
Radio  is  a  medium  of  information that  has  been  known  for  a  long  time. Besides  as  information  medium,  radio  can  also  be  used    medium  of  entertainment  for the  community  .  With  the  ease  and  "mercy  "  in  use  ,  the  radio  became  one  of  the selected alternative for entertainment as well as to access information around .   The objective in this study was to analyze the internal and external factors that include  (  strengths  and  weaknesses  and  the  potential  opportunities  and  threats magnitude  )  in  determining  what  is  the  right  competitive  strategy  applied  to  the  radio Voice of Salatiga in the face of competition . This study used a qualitative descriptive - quantitative, in which the data obtained directly from the radio Voice Salatiga, as well as interviews with relevant parties and obtained from the study of literature .   The  author  uses several  analytical  methods  Research  is  used,  the  first  is  the matrix analysis Internal- External ( IE ) used to determine the value  weighted on each of the factors, both internal and external , then the authors explain in more detail about how  the  opportunities  and  threats  radio  Salatiga  sound  with  matrix  analysis  SWOT   ( Strength , Weakness, Opportunity , Threat ) . IE  matrix  analysis  results  of  the  matches  between  the  weighted  value  matrix IFE  and  EFE  matrix  produces  a  weighted  value  of  3.17292 and  2.79886  .  With  these results  put  the  radio  Voice  Salatiga  on  cell  matrix  IV  in  IE  ,  it  means  the  right competitive  strategy  applied  to  the  radio  Voice  Salatiga  namely  Stability  strategy,  in which this strategy can be executed with the maintain and nurture . Salatiga sound can implement  the  strategy  without  changing  the  direction  of  the  strategy  that  has  been implemented , tujuanya relatively defensive , that is by maintaining the trust of listeners to the brand and Imaj radio sound good to Salatiga